Can financial distress and good corporate governance influence tax aggressiveness - Sherlyn A.F Saputri; Wirawan E.D Radianto (Institute of Computer Science (IOCS), 2023)
This study aimed to test the impact of financial distress, audit quality, institutional ownership, and independent commissioners, which can be helpful for the government, DJP, and companies as a consideration in identifying matters that influence tax aggressiveness. Sampling used a purposive sampling method so that the company data sample in this study totaled 29 property and real estate companies listed on the Indonesia Stock Exchange from 2014-2020. Methods of data analysis using multiple regression analysis with robust standard error. The results of this study indicated that financial distress, audit quality, and independent commissioners have no impact on tax aggressiveness, and institutional ownership has a negative impact on tax aggressiveness. Thus, the healthiness or bankruptcy of a company's financial condition, audited by a Big 4 KAP or non-Big 4 KAP, and the high or low number of idependent commisioner. It does not affect a company's decision to carry out tax aggressiveness. Instead, tax aggressiveness will decrease as institutional parties' shareholdings increase.